A prospective and consecutive study assessing short-term clinical and radiographic outcomes of Chinese domestically manufactured 3D printing trabecular titanium acetabular cup for primary total hip arthroplasty: evaluation of 236 cases - Chen, Guo; Wang, Chen Yi; Ma, Zou; Yi, Hong Lin; Bi, Na Meng; Zhu, Wei Jiang; Han, Jie; Lu, Sha Li; Zhang, Shang Shang; Shen, Hai; Zhang, Wu Hui; Zhang, Peng; et al. (Frontiers in Surgery, 2024)
Purpose We prospectively evaluate the short-term clinical and radiographic outcomes of the only Chinese domestically produced trabecular titanium acetabular cup(3D ACT™ cup) in primary total hip arthroplasty (THA), aiming to provide evidence-based support for its clinical application. Methods A total of 236 patients, who underwent primary THA using 3D ACT™ cup in the Department of Joint Surgery at our hospital between January 2017 and June 2019, were included in this study. General patient data, imaging information, functional scores, and complications were collected to evaluate the early clinical efficacy. Results All patients were followed up for 33-52 months, with an average of (42.2±9.2) months. At the last follow-up, the preoperative HHS score increased significantly from 43.7±6.8 to 85.6±9.3 points (P<0.01). Similarly, the preoperative WOMAC scores showed significant improvement from 59.2±5.8 to 13.1±3.5 points (P<0.01). 92.3% of the patients expressed satisfaction or high satisfaction with the clinical outcome. Furthermore, 87.7% of the acetabular cups were positioned within the Lewinnek safe zone, achieving successful reconstruction of the acetabular rotation center. The cup survival rate at the last follow-up was 100%. Conclusions The utilization of the only Chinese domestically manufactured 3D printing trabecular titanium acetabular cup in primary THA demonstrated favorable short-term clinical and radiographic outcomes. The acetabular cup exhibits excellent initial stability, high survival rate, and favorable osseointegration, leading to a significant enhancement in pain relief and functional improvement. In the future, larger sample sizes and multicenter prospective randomized controlled trials will be required to validate the long-term safety and effectiveness of this 3D ACT™ cup.